Functional analysis of stance nouns in English Language Teaching research articles. Issue 4 (2nd October 2022) - Ebrahimi, Seyed Foad; Mohsenzadeh, Abdollah
Abstract: The study of stance as a linguistic feature that conveys the attitude of writers to their materials and readers has become an important research area. The head noun in noun complement structures is one of the overlooked means of stance. This study aims to explore the frequencies, forms and functions of such a structure in a sample of 50 research articles from the discipline of English Language Teaching (ELT). The classifications of stance nouns proposed by Jiang and Hyland were used to meet the study objectives. According to the results, stance nouns were more frequent in this study compared to studies reviewed in literature, suggesting the impact of disciplinary conventions. Also, the findings indicated that the attribute class of stance was the most frequent, pointing to the intention of ELT writers to use stance nouns to make judgments and evaluations. In addition, the findings showed that stance nouns were dominant in the of-preposition structure. In conclusion, the findings of this study could act as a guideline to include stance nouns in the syllabus for teaching research article writing in ELT and relevant disciplines.